Two phase flow boiling pressure drop in small channels - Sardeshpande, Madhavi V.; Shastri, Parikshit; Ranade, Vivek V. (IUTAM Symposium on multiphase flows with phase change: challenges and opportunities, 2015)
Two-phase pressure drop, flow instability and boiling regime identifications are an essential step in the design of a variety of plant in the power and process industries. Despite the wide spread applications, significant experimental data on flow boiling in small channel is not available. In the present work, experimental set-up was designed for studying boiling flows in 19 mm ID tube and identifies flow regimes at various mass and heat flux conditions by varying inlet fluid temperature. The steady-state pressure data was collected and flow regimes identified using pressure drop and pressure fluctuations inside the channel. (C) 2015 The Authors. Published by Elsevier B.V.
Keywords: flow boiling; flow instability; pressure drop; regime identification